PD-L1 on peripheral blood T lymphocytes is prognostic in patients with non-small cell lung cancer (NSCLC) treated with EGFR inhibitors. (March 2016) - Meniawy, Tarek M.; Lake, Richard A.; McDonnell, Alison M.; Millward, Michael J.; Nowak, Anna K.
Highlights: We examined the immune effects of EGFR inhibitors in patients with lung cancer. We found that higher PD-L1 on peripheral T cells was associated with worse outcomes. PD-L1 on T cells may be a potential biomarker to select patients for PD-1 inhibitors. Abstract: Objectives: The immune effects of EGFR tyrosine kinase inhibitors (EGFR-TKIs) are poorly understood. Identifying immune biomarkers could guide patient selection and optimisation of EGFR-TKI-immunotherapy combinations. Materials and methods: 33 patients with NSCLC treated with an EGFR-TKI were prospectively enrolled. Peripheral blood mononuclear cells were collected pre-treatment, and after 1, 3 and 8 weeks. Flow cytometry was used to identify immune cell subsets, including PD-1 and PD-L1 expressing T cells. Immune parameters were correlated with clinical outcomes. Results: Compared to healthy donors ( n  = 10), patients had higher pre-treatment proportions of proliferating and PD-L1 + CD3 + T cells ( p  < 0.001). Compared to patients with an EGFR mutation ( n  = 12), patients without a known mutation ( n  = 21) had higher proportions of proliferating CD4 + and PD-L1 + CD3 + T cells ( p  = 0.03). There was a significant increase in PD-L1 + T cells after 1 week of EGFR-TKI in patients whose disease progressed compared to non-progressors. Patients with higher PD-L1 + CD3 + T cells at 1-week were more likely to progress (OR 30.3, p  < 0.01) and had shorter PFS (1.6 vs. 8.8 m; p  < 0.01) and OS (3.8 vs 23.2 m; p  < 0.001) than those with fewer PD-L1 + CD3 + T cells. On multivariate analysis, high PD-L1 + CD3 + T cells was the only independent predictor for PFS (HR 3.7, p  = 0.01), while for OS independent predictors were high PD-L1 + CD3 + T cells (HR 6.5, p  < 0.01) and EGFR-negative status (HR 3.3, p  = 0.04). Conclusions: There was a significant correlation between PD-L1 expression on peripheral T cells and clinical outcomes in EGFR-TKI-treated NSCLC. This warrants further validation as a blood-based biomarker that may identify candidates for PD-1 inhibitors or immunotherapy-EGFR-TKI combinations.